Bahasa Indonesia di Era Digital: Analisis Pengaruh Penggunaan Media Sosial Terhadap Komunikasi Formal di Lingkungan Perkantoran - Gaidzimullah, Gaidzimullah; S, Delia; Fauzan, Dimas Akmal; Hasna, Fairuz; Aritonang, Gita Cintya Devi; Rizkyanfi, Mochamad Whilky (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to analyze the influence of social media on the use of the Indonesian language in formal communication in the workplace, particularly in the Bandung area. This study uses a descriptive qualitative method. Data collection was conducted using an interview guide, which is a list of questions arranged according to the research topic to systematically explore information. The data obtained is analyzed through three stages, namely data reduction, data presentation, and conclusion drawing. The results of the study show that conflicts caused by differences in language styles tend to be rare, as there is a mutual understanding regarding the applicable communication ethics. The use of informal language is still commonly found, especially in communication with close friends or familiar coworkers, while still paying attention to the applicable ethics in a professional context. On the other hand, formal language is still used in official situations, such as in meetings, report writing, and communication with superiors and clients. Overall, it is important to use Indonesian that adheres to the rules, manage communication well, and choose the right language to ensure professionalism, clarity of communication, as well as to maintain self-image, harmony, and productivity in the workplace